(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article reveals the concept and regulatory framework of the "Single Window" mechanism, presents an analysis of international experience on the successful and effective implementation of this mechanism (for example, Singapore, Sweden, the EU, Thailand, Mozambique). The problems arising during the implementation of the single window concept are presented, the solution of problematic issues arising in practice is proposed, and a number of recommendations are given for the successful implementation of the single window mechanism